Síndrome de Peutz-Jeghers: tratamento da lentiginose oral com laser Alexandrita Peutz-Jeghers Syndrome: treatment of oral lentiginosis with Alexandrite laser - Cristina Mansur; Leonora Mansur; Renata Côrtes Gonçalves; João Mansur; Aloísio Couri Gamonal; Rodolpho Valverde (Sociedade Brasileira de Dermatologia, 2003)
Descreve-se o caso de uma paciente de 10 anos de idade, com síndrome de Peutz-Jeghers, que há oito anos apresentava manchas escuras nos lábios. As lesões da mucosa oral foram tratadas com laser de Alexandrita 755 nm, de pulso longo(3ms),com bons resultados estéticos. We describe the case of a 10-year-old patient with Peutz-Jeghers Syndrome associated with brown melanin spots on the lips and onset 8 years previously. The oral lesions were treated using a long-pulse (3ms) Alexandrite 755 nm laser, with good results.